Drug delivery systems in periodontitis: A visualization and bibliometric analysis - Xia Chen; Xiaoping Liao; Yu Luo; Xiaoyan Zou; Hui Ji; Mingji Yang; Fang Ye (Saudi Dental Journal)
Objective: This study aimed to evaluate research hotspots and trends in the field of periodontitis and drug delivery systems from the perspective of bibliometrics. Methods: Publications related to periodontitis and drug delivery systems between 2001 and 2023 were retrieved from the Web of Science Core Collection database. Bibliometric analysis was conducted using VOSviewer, CiteSpace, and the R package “bibliometrix.” Results: A total of 299 articles from 46 countries, primarily India and China, were included in the analysis, and the number of articles related to periodontitis and drug delivery systems were found to be increasing annually. Silpakorn University, the Government Dental College and Research Institute, and the Indian Institute of Technology were identified as the main research institutions investigating the topic, while the Journal of Periodontology emerged as the most popular and co-cited journal in this field. Among the authors of these articles, Thawatchai Phaechamud published the most papers and Gary Greenstein was the most co-cited author. The development of more suitable treatment methods for periodontitis and materials for developing drug delivery systems is a major focus in this research field, with “implants,” “efficacy,” “nanoparticles,” and “mucoadhesive” being the main emerging research hotspots. Conclusion: To the best of our knowledge, this is the first comprehensive bibliometric study summarizing research trends and developments in the field of periodontitis and drug delivery systems. This information elucidates the latest research frontiers and can assist in conceptualizing new directions in research on periodontitis and drug delivery systems.